2001
DOI: 10.1007/bf02988502
|View full text |Cite
|
Sign up to set email alerts
|

Retention mechanism of hypoxia selective nuclear imaging/radiotherapeutic agent Cu-diacetyl-bis(N 4-methylthiosemicarbazone) (Cu-ATSM) in tumor cells

Abstract: The retention mechanism of the novel imaging/radiotherapeutic agent, Cu-diacetyl-bis(N4-methylthiosemicarbazone) (Cu-ATSM) in tumor cells was clarified in comparison with that in normal tissue in vitro. With Cu-ATSM and reversed phase HPLC analysis, the reductive metabolism of Cu-ATSM in subcellular fractions obtained from Ehrlich ascites tumor cells was examined. As a reference, mouse brain was used. To determine the contribution of enzymes in the retention mechanisms, and specific inhibitor studies were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
125
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 23 publications
2
125
0
Order By: Relevance
“…However, for Cu-ATSM this redox trapping is sensitive to the level of cell oxygenation, occurring most rapidly in hypoxic cells, leading to investigation of [ 60,64 Cu[Cu-ATSM as a marker of tissue hypoxia [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for Cu-ATSM this redox trapping is sensitive to the level of cell oxygenation, occurring most rapidly in hypoxic cells, leading to investigation of [ 60,64 Cu[Cu-ATSM as a marker of tissue hypoxia [26][27][28][29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…1), have shown promise as PET radiopharmaceuticals for imaging tissue perfusion (Cu-PTSM, Cu-ETS) [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and hypoxia (Cu-ATSM) [26][27][28][29][30][31][32]. The clinical utility of Cu-PTSM for quantifying perfusion in high-flow tissues, such as hyperemic myocardium, appears limited by the high affinity of this chelate for HSA, a result not predicted by the promising results from canine models [13].…”
Section: Introductionmentioning
confidence: 99%
“…In brain, 70-80% of Cu-PTSM and Cu-ATSM was reduced by mitochondria, while in a variety of cancer cell types, mitochondrial retention is reported to represent approximately 10% of the total [82,[100][101][102]. Thus far, reduction of these complexes has only been investigated in individual subcellular fractions [100,[103][104][105], rather than intact tissues which have been exposed to copper complexes and then fractionated. Errors in accounting for relative differences in volumes and concentrations of each fraction potentially skew the measured contribution of each fraction to total cellular bioreduction, but some tissue-specific differences have been identified nonetheless.…”
Section: What Is the Intracellular Site Of Complex Reduction?mentioning
confidence: 99%
“…They demonstrated that this reduction was inhibited in a dose-dependent manner by the flavin enzyme inhibitor DPIC, and pHMB, a thiolenzyme inhibitor, suggesting that cytosolic electron transport chain enzymes were responsible. Further evidence for this was provided by treatment of microsomal fractions with inhibitors of cytochrome b5 reductase and cytochrome P450 reductase, resulting in inhibition of tracer reduction [101].…”
Section: What Is the Identity Of The Bioreductants?mentioning
confidence: 99%
“…The mechanism responsible for 64 Cu-ATSM retention is not completely understood, but in vitro studies have indicated that the 64 Cu-ATSM complex undergoes reduction by free diffusion after entering the cells (27)(28)(29). In normoxic cells, 64 Cu-ATSM is rapidly reoxidized and consequently able to leave the cell again by free diffusion.…”
mentioning
confidence: 99%